(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The article deals with the problem of training future officers for professional activity based on the acmeological approach. The description of the methodology, as a science of acmeology, as the basis of the acmeological approach is given. The choice of this approach is justified, and it is explained by the fact that each new achievement is focused on the development of professional skills, it happens when tasks and goals are gradually made more difficult, but within the limits of what is available, so that they can be fulfilled. This approach provides a transition from one acme (peak) to another more complex one, which provides the ability to meet the needs in the performance of tasks, but does not discourage the desire to work and achieve new achievements. The possibility of improving the quality of training due to the introduction of acmeological technologies, which provide pedagogical conditions for the professional growth of future officers through the creation of an integration system of training, is considered. The reasons for the introduction of the acmeological approach to the training of future officers have been determined, resulting from the identified contradictions between: the needs of the Armed Forces of Ukraine for professionally competent officers and the level of their training for professional activities at the Higher Education Institution; the introduction of methodological approaches into the educational process and the need for their implementation, in particular the acmeological approach. It was determined that the acmeological approach contributes to better training of specialists, which consists in: providing a more detailed study of the personal qualities of a specialist; correct selection of various types of pedagogical conditions for the organization of the educational process; designing plans for conducting ascertainment and formative experiments; correct organization and conduct of independent educational and cognitive activities.